A DISCOURSE ANALYSIS OF CLASS INTERACTIONS - Elena UNGUREANU (National Centre for Policy and Evaluation in Education, 2020)
In this article I analyse the discursive context of two classes of students bringing into discussion the concepts of educational knowledge and the organization of teaching-learning activities. Although there is much research that provides nuanced insights into how teachers and students are involved in the social construction of classroom discourses about knowledge, in Romanian literature the issue of classroom interactions has been approached from the perspective of teachers ' and students' perceptions, while school knowledge has been studied only incidentally Therefore, I present a qualitative study, based on a critical discourse analysis that highlights how different versions of knowledge are socially constructed in the discursive space of the classroom, in order to point out ways in which the classroom and school can become spaces in which interactions no longer revolve around knowledge defined only by reference to disciplinary content. Bimonthly observations and audio-video recordings were made in the 2017-2018 school year during language and communication activities, in two classes, from two different schools. The results show that classroom interactions and participation structures differ depending on the purpose of the activities, and student participation is not only based on generally accepted communication rules, but varies depending on the implicit or explicit purpose of the activities.